Encapsulating MWNTs into hollow porous carbon nanotubes : a tube-in-tube carbon nanostructure for high-performance lithium-sulfur batteries - Wu, Wangliang (2014)
A tube-in-tube carbon nanostructure (TTCN) with multi-walled carbon nanotubes (MWNTs) confined within hollow porous carbon nanotubes is synthesized for Li-S batteries. The structure is designed to enhance the electrical conductivity, hamper the dissolution of lithium polysulfide, and provide large pore volume for sulfur impregnation. As a cathode material for Li-S batteries, the S-TTCN composite with 71 wt% sulfur content delivers high reversible capacity, good cycling performance as well as excellent rate capabilities.